Modeling air pollution using distance based ranking fuzzy numbers approach / Mohamad Idham Md Razak … [et al.] - Md Razak, Mohamad Idham; Ahmad, Prof. Dr. Ismail; Mohd Amir Hamzah, Afzan Sahilla; Ibrahim, Raihan; Hong, Fang Jing @ NurSyaifa (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Air pollutants can be either gases or aerosols which particles or liquid droplets suspended in the air. They change the natural composition of the atmosphere, can be harmful to humans and other living species and can cause damage to natural water bodies and the land. Anthropogenic specifically due to the human causes that in this study, it has been identified that Population, Gross Domestic Product (GDP) and Manufacturing Industry adaptive from IPAT Model are the major contributors to the emission of carbon dioxide. The major contribution of this study is by improving the IPAT's fuzzy dilemma into better model using Distance-Based Ranking Fuzzy Numbers Approach introduced by Ahmad Syafadhli Abu Bakar, Daud Mohamad, Nor Hashimah Sulaiman (2012). The paper was written as to enrich the field of Ranking Fuzzy Numbers (RFN) as RFN is recognized with its ability on solving numerous decision-making problems and has only being applied on Risk Analysis, Game Theory, Pattern Recognition and Artificial Intelligent. This study is the pioneer study using RFN in modeling Air Pollution measurement in Malaysia. The time series data gained and analyzed from the years 1970 to 2011 to explain the relationship among the carbon emission with the Population, Gross Domestic Product (GDP) and Manufacturing Industry. Hence, the forecasted value of Carbon emission can be used to assist the government in future planning and development.